Determining basic food quality using SAW - Hamid, Abdul; Sudrajat, Ajat; Kawangit, Razaleigh Muhamat; Don, Abdul Ghafar; Huda, Miftachul; Jalal, Burhanuddin; Akbar, Wahyu; Onn, Azura; Maseleno, Andino (International Journal of Engineering and Technology, 2018)
Basic food is an abbreviation of Nine Basic Ingredients, namely: rice/sago/corn, sugar, vegetables/fruits, beef/chicken/fish, milk, eggs, kerosene / LPG, cooking oil, and salt. To determine the quality of Basic food, many people still experience many obstacles, including the difficulty of distinguishing Basic food with good quality and Basic food with poor quality. So there is a need for artificial intelligence that can be used to determine the basic food quality that is suitable for consumption. With the existence of artificial intelligence, it is expected that ordinary people do not wrong to buy Basic food with good quality. This artificial intelligence was made by using the SAW method with the Visual Basic programming language.